PENYULUHAN SALAM BESTI (SELAMANYA BEBAS STUNTING) DESA KLEBET KEMIRI KABUPATEN TANGERANG - Kemiri, Kemiri; Dewi, Irma Dwi Puspita (Nindikayla Institute, 2023)
Stunting is a condition where the body's growth is hampered in children due to a lack of adequate nutrition, especially during the early growth period, namely the first two years. This condition usually occurs because children do not get enough nutrition, both in the amount and diversity of food needed for optimal growth. The aim of implementing the Community Work Lecture Program (K3) is to provide knowledge and insight about stunting prevention. As well as to increase public awareness and change people's behavior to live healthy lives. The method for implementing K3 is lectures, discussions and questions and answers to the people of Klebet Village Rt 1, 2, 3 Rw 1 who participate in Posyandu Pisang. Evaluation of this activity was carried out by looking at participants' understanding of stunting and related balanced nutrition. The evaluation results show that 65% of participants in Community Work Lecture (K3) activities understand stunting and balanced nutrition. It is hoped that public knowledge about stunting, especially proper stunting prevention, can reduce the risk of stunting problems in Indonesia